(3TQM MRH GdHMQs - (3Ydj Hf YHO Gddg GdTGPdj, fhQ GdOjf CHj GdMSf,J (B656 (3g` s
(3ChdgG (B:s
(3GYde Cf dMRH GdHMQ GaJJGMkG hGNJJGekG CYhP HGddg ef GdTjWGf GdQLje HSe Gddg GdQMef GdQMje jG Ydi jGYXje jG Mdje jGYdje CfJ QHi hYdec MSHi s
(3BNQgG (B:s
(3bhdg JYGdi (B( (3jMHhfge cMH Gddg hGdPjf BefhG CTO MHkG ddg (B) (3SHYjf eQI hHYOg jbhd Gdbi eMHJi ai bdH adGHf adGf aEPG JeJ GdOYhI jLYd GdeGA ai hYGA Ke HJhLg Edi GdeWdhH ajZSd hLgg HPdc GdeGA hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9321) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs